2018
DOI: 10.18203/2349-2902.isj20180830
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of patients with fibroadenoma of breast

Abstract: Background: Fibroadenomas of breast are the commonest benign breast conditions. It is an attempt to study this common condition.Methods: Fifty cases with histologically diagnosed cases of fibroadenoma were included in the study and were compared with previous data from literature.Results: All the fifty patients included in this study were indoor patients. Maximum number of patient were in third decade (64%). Urban females have higher incidence of fibroadenoma (72%). Most fibroadenoma are unilateral (86%). Fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…6 Laxman et al studied 50 patients and found 34% cases had upper lateral quadrant fibroadenoma. 11 The 8% of cases had lower medial quadrant fibroadenoma, 26% patients had fibroadenoma in lower lateral quadrant, 20%, patients had fibroadenoma in upper medial quadrant.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…6 Laxman et al studied 50 patients and found 34% cases had upper lateral quadrant fibroadenoma. 11 The 8% of cases had lower medial quadrant fibroadenoma, 26% patients had fibroadenoma in lower lateral quadrant, 20%, patients had fibroadenoma in upper medial quadrant.…”
Section: Discussionmentioning
confidence: 86%
“…Minimum cases (14%) had giant fibroadenomas. 11 The various diagnosed benign breast diseases in study subjects are discussed in Table 5. Out 200 cases studied, 103(51.5%) patients had fibroadenoma, 64 (32%) were fibroadenosis, ductal ectasia was found in 10 (05%), Breast abscess was in 06 (03%) cases, 7 (3.5%) cases had phylloids and remaining 10 (5%) cases had mastitis.…”
Section: Discussionmentioning
confidence: 99%
“…The condition is probably caused by the hormone estrogen, which affects the proliferation of the breast lobular ductal epithelium 19 . Laxman et al found that the most common type of FAM encountered, or around 84%, is pericanalicular 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Fibroadenoma raksasa dapat menyebabkan payudara yang asimetri, distorsi kulit di atasnya dan peregangan puting. 7 Perempuan yang menderita fibroadenoma mammae dapat mengalami gangguan psikologis yang cukup besar, beban finansial, kehilangan pendapatan, dan komplikasi kesehatan lebih lanjut. 6,8 Etiologi dan patogenesis FAM masih belum jelas disebabkan banyak predisposisi yang komplek atau multifaktorial, tetapi penjelasan umum yang digunakan adalah kadar hormon, obesitas dan riwayat keluarga.…”
Section: Pendahuluanunclassified
“…Usia yang banyak dilaporkan adalah 17-30 tahun. 14,16,17,19 Karakteristik pasien FAM yang datang ke poli bedah sebagian besar memiliki profil benjolan terasa nyeri tekan, demam, 13,14 benjolan FAM umumnya muncul di kuadran lateral atas atau luar atas dari payudara kiri 7,14,17,20 dengan ukuran kecil dan terus tumbuh menjadi besar seiring berjalannya waktu. Karakteristik ini perlu menjadi bagian materi pendidikan kesehatan sejak dini.…”
Section: Metodologiunclassified